Donald Trump, Jerusalem and the forecast of Ibn Barrajan - ., Sofiandi; ., Siti Marpuah; Hasyim, Inayatullah (Penerbit UTHM, 2020)
Hours after US President Donald Trump announced that the United States would move its Israeli embassy to Jerusalem, countries from Indonesia to Malaysia, as well as its allies, form France to Britain, explicitly condemned the move. This unpopular decision reverses decades of American policy in the Middle East. As a consequence, Americans in Turkey, Germany, and through the region were warned by local US embassies to be cautious after the decision, and American children in Jordan told not to go to school. Hundreds were wounded during protests in Gaza and the West Bank, and militant group Hamas called Trump’s announcement a “declaration of war”. The conflict and the communal confusion caused by this declaration has further reinforced the position of the old city which is very special for Israel and Palestine, as well as for the three major world religions, namely Islam, Christianity and Judaism, the three religions that are equally related to the Abrahamic or Ibrahim figure in the books of holy. Various predictions and views about the end of the story of the conflict are emerging in various forms of perspective. In the Islamic one, the "prediction" of liberation of Palestine and Al-ASuraha is not absurd, but derived from the Qur'an, hadiths of the Prophet SAW, atsar as-sahabah and various events of Islamic history of all time. One of the highlights is predicted by Ibn Barrajan. This short article explores the present phenomenon with what Ibn Barrajan had predicted in relation to the issue of Jerusalem.